2008
DOI: 10.3324/haematol.11575
|View full text |Cite
|
Sign up to set email alerts
|

Tumor lysis syndrome in patients with acute myeloid leukemia: identification of risk factors and development of a predictive model

Abstract: BackgroundDespite the prophylactic use of allopurinol, tumor lysis syndrome (TLS)-related morbidity and mortality still occur in a number of patients with acute myeloid leukemia (AML). The aim of this study was: (i) to analyze the incidence and outcome of TLS in a large series of patients with AML receiving hyperhydration and allopurinol, (ii) to identify risk factors for TLS, and (iii) to develop a prognostic scoring system for estimating individual risk of TLS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
133
1
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(150 citation statements)
references
References 28 publications
7
133
1
9
Order By: Relevance
“…The same pitfalls can be observed in a more recent retrospective study performed in a larger series of adult AML patients. 28 TLS is not a frequent complication in the treatment of adult solid tumors. 29,30 High-risk tumors include cancers known to be highly sensitive to chemotherapy, like bulky small cell lung cancer and metastatic germ cell carcinoma (either gonadal or extragonadal).…”
Section: Recommendationsmentioning
confidence: 99%
“…The same pitfalls can be observed in a more recent retrospective study performed in a larger series of adult AML patients. 28 TLS is not a frequent complication in the treatment of adult solid tumors. 29,30 High-risk tumors include cancers known to be highly sensitive to chemotherapy, like bulky small cell lung cancer and metastatic germ cell carcinoma (either gonadal or extragonadal).…”
Section: Recommendationsmentioning
confidence: 99%
“…Available facts suggest that the incidence of clinical TLS is approximately 3-7% for acute leukemias and 4-11% for lymphomas (Annemans et al, 2003;Wossmann et al, 2003). However certain subgroups of leukemia patients, such as those with mature B acute lymphoblastic leukemia (ALL) and Burkitt's lymphoma/ leukemia, have been reported to have a high frequency of TLS of around 25% (Stapleton et al, 1988;Montesinos et al, 2008). Table 4 summarizes the degrees of risk in patients with a particular type of cancer.…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%
“…A study at our institution retrospectively examined 194 patients with acute myeloid leukemia, of whom 19 developed clinical or laboratory TLS. In univariate analysis, a strong association was demonstrated between baseline creatinine level and the development of TLS {odds ratio (OR), 31 (33,(37)(38)(39). Table 3 summarizes these additional risks.…”
Section: Identification Of Individuals At Riskmentioning
confidence: 99%
“…The association between renal function and development of TLS is strong and has been seen across a variety of populations and tumor subtypes. A prospective study of 1192 patients with non-Hodgkin lymphoma (of whom 63 developed TLS) revealed preexisting renal dysfunction in 68% of those affected; however, (37). Further studies using estimated GFR rather than creatinine concentration will help to better elucidate differences in risk among varying degrees of kidney function while minimizing potential confounding by sex and race.…”
Section: Effect Of Kidney Functionmentioning
confidence: 99%